Pelatihan Manajemen Masjid Baitul Muttaqin menuju Masjid Mandiri dan Berdaya - Muarif, Ahmad Dalhar (Kifah: Jurnal Pengabdian Masyarakat, 2025)
A mosque is not only a place of worship but also serves as a center for social, educational, and economic activities within the Muslim community. Effective management is essential for mosques to become independent and empowering institutions. This community service program was conducted at Baitul Muttaqin Mosque, Pakis Village, Tambakromo District, Pati Regency, using the Asset Based Community Development (ABCD) approach. The activity involved training in mosque management with the participation of lecturers, IPMAFA KKN students, mosque administrators, and congregants. The training materials included mosque management theory, the use of technology, youth empowerment, and strategies for achieving financial and organizational independence. The activity had an impact on increasing the understanding of the management regarding the importance of modern mosque management, a commitment to conduct benchmarking visits to independent mosques, more than 80% stated their desire to improve mosque management based on independence. This program marks an important step toward transforming Baitul Muttaqin Mosque into a more professional, transparent, and sustainable institution.